EFEK DETERMINASI UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PROPERTY DAN REAL ESTATE - Ilham, Muh.; Sjahruddin, Herman; Data, Muhammad Umar; Pascawati, Poppy Nahdia Syahrani (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2021)
The company's profitability is not only a major factor in the creation of firm value, several previous researchers have explored the determinants of firm value creation. This statement becomes an argument so that this study re-examines the contribution of firm size and leverage to the firm's value of property and real estate. The selection of issuers relies on the criteria sampling technique by utilizing financial reports obtained from the Indonesian capital market directory for the 2017-2019 period, there are thirteen issuers' financial reports that cannot be used from forty-two issuers, that meet the criteria so that only eighty-seven units of analysis are left. data. The results of the analysis of variance show that a large company size cannot make a meaningful contribution to increasing firm value. This condition is different from leverage, in that high leverage is proven to be able to make a significant contribution in increasing firm value.